Pendampingan Penyusunan Laporan Keuangan Sederhana bagi Pelaku Usaha Derbi Beauty Glow (DBG) - Anggreni, Meilinda; Nurpratiwi, Tiara; Carolina, Dessy; Syafitri, Twenty Mariza (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This community service activity aims to provide understanding and training to the managers of Derbi Beauty Glow (DBG), located on Jl. Tanjung Barangan, Palembang City, regarding the importance of preparing financial reports as part of accountable and sustainable business management. The activity was conducted on July 1, 2025, at 1:30 PM WIB and was attended by the business owner. The activity included educational sessions and practical training covering basic understanding of financial statements, recording of income and expenditure transactions, and the preparation of a simple profit and loss statement. The results of the activity showed an increase in participants' knowledge and skills in systematically preparing business records, which is expected to support decision-making and business sustainability through more organized and informative financial management.